Puan Mimi Sintia Mohd Bajury unveils legal insights on sexual harassment - UiTM, Faculty of Law (Faculty of Law, 2023)
An insightful session is marked as Puan Mimi Sintia Mohd Bajury, a senior lecturer from the Faculty of Law at Universiti Teknologi MARA, takes the spotlight on the talk show program 'Apa Khabar Malaysia' airing live on February 17, 2023, from 9:00 AM to 10:00 AM. Puan Mimi delves into the intricate world of legal perspectives on the pervasive issue of sexual harassment. Her expertise sheds light on this prevalent concern. This informative discussion is available on various platforms, including Astro Channel 502, Unifi TV Channel 631, MyFreeview Channel 121, and YouTube Live BERNAMA TV. Those who tune in have the opportunity to gain valuable insights from a legal expert.